The Impact of Attracting High Level Management Competencies` Strategies on the Performance of Employees On Iraqi Commercial Banks - Kamil Oudah, Bilal; Ebrahem Ahmad, Othman; Edan, Ahmad (Opción, 2019)
This study aimed to determine the impact of Attractive competencies strate- gies on the performance of cmployees on Iraqi commercial banks, which in- cluded the study population all Kuwaiti banks listed on the Kuwait Financial, shares of nine banks, while the study sample of (9) responsive. has adopted a researcher on exporters Presidents of data collection are the primary data and secondary data. Hypotheses were tested using simple linear regression analysis and multi. The study concluded that there is a statistically significant effect of the dimensions of the process of attracting qualified senior management of (b determine plans to attract senior management competencies, and know edge sources to attract qualified senior management) on the performance of em- ployees in commercial banks. And in the light of the results of the study made a number of recommendations including: pay attention to the development of the capacity of managers in the field to attract qualified senior management in banks surveyed by preparing training programs and use of experts and con- sultants in the field of attracting talent. And to build on the foundations of the process and objectivity in determining the quality of the Supreme Administra- tive efficiencies and suitability to the circumstances, and when depolarized in the banks surveyed, which positively affect the performance of the employees.